Technology-Enhanced Learning (TEL): How Does It Affect Pre-Service Mathematics Teachers? - Rani Rizka Ramdani; Kana Hidayati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The rapid advancement of ICT has fundamentally reshaped the educational landscape, creating a critical need for educators to be proficient in technology integration. This study investigates the influence of Technology-Enhanced Learning on the professional development of pre-service mathematics teachers, focusing on its impact on their teaching competencies and overall readiness. This research employs a systematic literature review, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Twenty-six relevant articles published between 2017 and 2025 were identified from six academic databases for in-depth analysis. The findings were categorised into cognitive, affective, and psychomotor domains. The results reveal that TEL significantly enhances PMTs' cognitive abilities, such as conceptual understanding, problem-solving, and reasoning skills, while also improving motivation, self-efficacy, and confidence in the affective domain. In the psychomotor domain, it develops essential technical competencies, creativity, and readiness for technology-based teaching. In conclusion, integrating TEL is pivotal for modern teacher education programs. It not only equips future mathematics teachers with the necessary 21st-century skills but also fosters a positive disposition towards technology in the classroom. Future research should conduct empirical studies to explore the pedagogical potential of emerging technologies for strengthening digital literacy, creativity, and pedagogical innovation among pre-service mathematics teachers.